Formation of acrylamide during the roasting of chia seeds (Salvia hispanica L.). (1st February 2023) - Mesías, Marta; Gómez, Pablo; Olombrada, Elena; Morales, Francisco J.
Highlights: Roasting of chia seeds led to acrylamide formation. Acrylamide formation depended on the physical integrity of the chia seed. Acrylamide formed rapidly on the seed coat but extensively in the inner part. Acrylamide content in the coat only represented 20–25% of the whole seed. Addition of roasted ground chia seeds to foods should be revised. Abstract: Chia is a novel food rich in health-promoting constituents. There is concern regarding the formation of process contaminants when subjected to thermal processing. Acrylamide formation in chia seeds under different roasting conditions (160–200 °C/5–30 min) and formats (whole seeds and ground seeds) was investigated. Acrylamide increased with the intensity of the thermal treatment until a maximum at 180 °C/15 min where levels of precursors were significantly reduced. The fate of acrylamide formation also depended on the physical integrity of the chia seed. Acrylamide formed rapidly on the coat of the seed but represents only 20–25 % of the total. Acrylamide was generated progressively in the inner part of the cell and efficiently retained by the pericarp. The particle size and integrity of chia seeds should be considered in food applications subjected to thermal treatment and grinding or the addition of ground seeds should be revised to reduce the exposure of acrylamide to consumers.